A Statistical Method for Detecting Gravitational Recoils of Supermassive Black Holes in Active Galactic Nuclei. Issue Volume 12:Issue S324(2016) (23rd June 2017) - Raffai, P.; Bécsy, B.; Haiman, Z.; Frei, Z.
Abstract: We propose an observational test for gravitationally recoiling supermassive black holes in active galactic nuclei, based on a positive correlation between the velocities of black holes relative to their host galaxies, |Δ v |, and their obscuring dust column densities, Σdust, both measured along the line of sight. Our findings using a set of toy models implemented to a Monte Carlo simulation imply that models of the galactic centre and of recoil dynamics can be tested by future observations of the potential Σdust –|Δ v | correlation. We have also found that the fraction of obscured quasars decreases with |Δ v |, for which the predicted trend can be compared to the observed fraction of type II quasars, and can further test combinations of models we may implement.